The influence of systemic team coaching on diversity and inclusion management in corporate South Africa - Segalo, Thuli Nokuphiwa (My University, 2022)
In the multicultural South African (SA) organisational context, effective diversity and inclusion (D&I) management is an organisational imperative. Organisations are challenged with finding effective and sustainable ways to manage D&I. Multicultural teams are at the centre of providing innovation and creativity value for organisations. The ineffective management of D&I has consequences for organisations, such as, increased grievance complaints, declining employee engagement, negative impacts on talent management, and ultimately, impacts the organisation’s competitive advantage and performance. This study explores the influence of systemic team coaching (STC) on D&I management in SA organisations. This was a mixed-methods study that used a sequential explanatory design and had two distinct phases: quantitative and qualitative. The quantitative data acquired via a survey questionnaire was analyzed using partial least squares structural equation modeling (PLS-SEM). Semi-structured interviews were conducted to acquire qualitative data, which were subsequently subjected to thematic analysis. The results and findings were integrated utilising joint display analysis. The study found that key diversity and inclusion enabling elements are inherent in the experience accounts of team coaching by managers and teams. Team coaching enabled the facilitation of increasing team awareness, building trust and psychological safety, creating space for team members to feel heard, and valued. The study contributes valuable insights for HR professionals and leaders in how STC contributes to the effective management of D&I. The study adds knowledge on team coaching, team effectiveness, D&I management. The study concludes that STC is a practical intervention which enables the support of organisational teams to effectively manage D&I complexities.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Business and Executive Coaching to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2022
Keywords: Systemic Team Coaching; Diversity; Inclusion; Diversity management; Inclusion management; Transformation; Multicultural teams; SDG-8: Decent work and economic growth